Morphologic Evaluation of the Patella: The Impact of Gender and Age - Nguyen TT; Le HDT; Hoang NT; Le TB; Ha TH (Orthopedic Research and Reviews, 2024)
Thanh Thao Nguyen,1 Hoang Di Thu Le,2 Ngoc Thanh Hoang,1 Trong Binh Le,1 Thi Hien Ha1 1Department of Radiology, Hue University of Medicine and Pharmacy, Hue University, Hue, Vietnam; 2Department of Radiology, Oncology Hospital, Da Nang, VietnamCorrespondence: Thanh Thao Nguyen, Department of Radiology, Hue University of Medicine and Pharmacy, Hue University, Hue, Vietnam, Email ntthao@hueuni.edu.vnIntroduction: The patellofemoral joint is a complex joint that plays a crucial role in knee joint function and stability. This study aims to describe the MRI characteristics of the patellofemoral joint in Vietnamese adults.Subjects and Methodology: A cross-sectional study was conducted on 280 patients at Hue UMP Hospital from May 2020 to May 2021. All patients underwent knee MRI using Siemens Magnetom Amira 1.5 Tesla. The evaluation parameters included the morphology of the patella and the femoral trochlea.Results: The study found that the morphological parameters of the patellar joint varied significantly between genders and age groups. The mean largest patellar transverse diameter was 4.26 ± 0.37 cm, the average length of the lateral joint facet was 2.5 ± 0.26 cm, and the medial joint facet was 2.0 ± 0.25 cm. The patellar height was 4.07 ± 0.35 cm. The indexes of patellar morphology were higher in men than in women, except for the lateral-medial facet ratio. The most common Wiberg classification was type B (63.9%), followed by type C (25.4%), and type A was the least common (10.7%). There was a statistically significant difference in the patellar measurements between different age groups. There was a weak negative linear correlation between the dimensions of the largest transverse diameter, the length of the articular surface, the patellar articular angle, and the age of the patient. Additionally, there was a moderate inverse linear relationship between patellar height and patient age.Conclusion: This study highlights the significant variations in patellar morphology based on gender and age. The findings emphasize the importance of careful assessment and consideration of these variations in the imaging evaluation of the patellofemoral joint.Keywords: patellofemoral joint, anterior knee pain, patellar morphology, Vietnamese, Insall-Salvati ratio